Detection of The Lipoatrophy of Lumbar Paraspinal Muscles Semi Quantitatively In Patients With Low Back Pain By TSE-T2W MR Sequence - Alicioglu, Banu; Demirbag Kabayel, Derya; Sut, Necdet; Emen, Sacit (Annals of Medical Research, 2021)
None